Pelatihan Pengisian SPT dengan Aplikasi Coretax untuk WPOP bagi Masyarakat RT 095 RW 008 Kelurahan Sukajaya Kecamatan Sukarami Kota Palembang - Mutiara Maimunah; Desy Lesmana; Delfi Panjaitan; Novita Febriany (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This study aims to improve the understanding and skills of individual taxpayers in using the Coretax application for reporting annual tax returns.Research Methodology: This study was conducted in RT 095 RW 008 Sukajaya Subdistrict, Sukarami District, Palembang, using a survey-based approach combined with training and mentoring methods. The activities included socialization, demonstration, and hands-on practice using the Coretax application. The tools used consisted of laptops or computers such as Acer, or Lenovo, smartphones, and projectors. The software used included the Coretax application, web browsers such us Google Chrome or Mozilla Firefox, and Microsoft Office. Data were collected through observation and questionnaires.Results: The results show that the activity was highly successful and effective, with an increase in participants understanding and skills averaging 4.70 in using the Coretax application, including account activation, login procedures, and tax return reporting.Conclusions: The training and mentoring activities were effective in improving digital tax literacy and participants’ technical abilities in using the Coretax system.Limitations: This study is limited to a specific location and a limited number of participants and does not measure long-term impacts.Contributions: This study contributes to improving digital tax literacy in the community and supports the implementation of the Coretax system, particularly for individual taxpayers.